2021
DOI: 10.22365/jpsych.2021.034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation tools of the characteristics of attention deficit and hyperactivity disorder (ADHD) in children and adolescents: A literature review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published during the production process, errors, may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The commission errors of IVA-CPT reflected the inhibition ability of impulse. The subjects had to suppress impulses instead of making mistakes when they received the visual and audiovisual combination stimuli ( 44 , 45 , 48 ). Therefore, it showed that real HD-tDCS can improve the inhibitory control of the subjects in addition to improving attention maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The commission errors of IVA-CPT reflected the inhibition ability of impulse. The subjects had to suppress impulses instead of making mistakes when they received the visual and audiovisual combination stimuli ( 44 , 45 , 48 ). Therefore, it showed that real HD-tDCS can improve the inhibitory control of the subjects in addition to improving attention maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…The IVA + CPT is a valuable tool for assessing ADHD ( 44 , 45 ). The first part of the test is the Visual Attention Test.…”
Section: Methodsmentioning
confidence: 99%
“…An important lesson which could be learnt of identifying, assessing and treating individuals with ADHD from early developmental stages is that it will serve for implementing future measures which will be useful when those individuals become adults diagnosed with this chronic disorder (Koumoula, 2012).…”
Section: Introductionmentioning
confidence: 99%